2004
DOI: 10.1300/j091v18n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sustainability Using Data from the Forest Inventory and Analysis Program of the United States Forest Service

Abstract: Forest sustainability has emerged as a crucial component of all current issues related to forest management. The seven Montreal Process Criteria are well accepted as categories of processes for evaluating forest management with respect to sustainability, and data collected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Indicators are then developed for each criterion to quantitatively or qualitatively assess current conditions and monitor changes over time. Criteria and indicators are not regulations but a framework for data collection and reporting (McRoberts et al 2004). Additionally, several types of third-party certification have been developed to provide unbiased assessment of sustainable forest management (Wingate and McFarlane 2005).…”
Section: Sustainable Forest Managementmentioning
confidence: 99%
“…Indicators are then developed for each criterion to quantitatively or qualitatively assess current conditions and monitor changes over time. Criteria and indicators are not regulations but a framework for data collection and reporting (McRoberts et al 2004). Additionally, several types of third-party certification have been developed to provide unbiased assessment of sustainable forest management (Wingate and McFarlane 2005).…”
Section: Sustainable Forest Managementmentioning
confidence: 99%
“…Among the eight attributes that the SFA used for constructing the EFI, the indicative value of growing stock volume, species composition, average tree heights, vertical structure, canopy density and the thickness of litters are well understood [32][33][34][35][36]. The indicative value of total vegetation cover and naturalness is less clear because their relationships with ecological functions have not been widely studied [31,37].…”
Section: The Strength and Limitations Of China's Monitoring Programmentioning
confidence: 99%
“…Each hexagon represents approximately 2428 ha and is systematically assigned to one of five interpenetrating, non-overlapping panels (Brand et al, 2000). Panels are measured on a rotating basis with targets of one panel per year in the eastern U.S. and one 50% sub-panel per year in the western U.S. (McRoberts et al, 2004). This design is derived from a global framework originally developed by the U.S. Environmental Protection Agency as part of the Environmental Monitoring and Assessment Program (EMAP) (Overton et al, 1990;White et al, 1992;US-EPA, 1997) and later implemented by FHM.…”
Section: Sampling Designmentioning
confidence: 99%
“…Phase 3 plots are assigned to one of five interpenetrating panels and are sampled once every five years. Comprehensive reviews of the FIA sampling strategy may be found in Brand et al (2000) and McRoberts et al (2004).…”
Section: Sampling Designmentioning
confidence: 99%